2022
DOI: 10.1021/acs.jced.2c00597
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibrium Measurements and Cubic-Plus-Association Modeling of Triethylene Glycol + Water + Methane Systems at 6.0 and 12.5 MPa

Abstract: As a part of a series of studies that aim to expand the experimental database used to assist the design of novel technologies in the field of subsea gas processing, 18 new vapor–liquid equilibrium data points were measured for the system triethylene glycol (1) + water (2) + methane (3) at 6.0 and 12.5 MPa, temperature range between 288 and 323 K, and a glycol content above 95 wt %. The new data include both gas [glycol (y 1) and water (y 2)] and liquid [methane solubility (x 3)] phase composition, with relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 23 publications
6
9
1
Order By: Relevance
“…Initial experiments were conducted at 40 °C to confirm that the results were consistent with the literature. As shown in Figure 3, our data is most consistent with that of Fisher et al 7 As noted recently by Trancoso et al, 5 the data from Jerinic et al 8 appears high. We were able to record only a single data point at a high pressure (134 bar) due to a loss of cylinder gas pressure.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Initial experiments were conducted at 40 °C to confirm that the results were consistent with the literature. As shown in Figure 3, our data is most consistent with that of Fisher et al 7 As noted recently by Trancoso et al, 5 the data from Jerinic et al 8 appears high. We were able to record only a single data point at a high pressure (134 bar) due to a loss of cylinder gas pressure.…”
Section: Resultssupporting
confidence: 92%
“…These authors concluded that the best approach was to use a new set of parameters with the 4F association scheme. The more recent papers from this research group however 4,5 confirm that the 4C data set proposed by Derawi et al 9 provides the best data fit when their more extensive experimental data set is used.…”
Section: T H Imentioning
confidence: 56%
See 3 more Smart Citations